GERAKAN #SAYAGOLPUT DALAM PEMILIHAN UMUM02019 - Fatimatuzzahro - -; Wijayanto - - (Journal of Politic and Government Studies, 2022)
In the 2019 Indonesian election, the SayaGolput movement appears by using social media to introduce this movement. This movement was initiated by ProDemocracy activists who chose not to vote or abstain in the 2019 election. This study focus on Pro-Democracy activists . This study uses a qualitative approach. Researchers explore data through in-depth interviews as primary data and secondary data is extracted through library research. This research shows that this movement was carried out in protest against the rulers of injustice. The simultaneous choice of abstentions is a controversial form of movement in the social media era. In the view of pro-democracy activists, abstain is a form of election boycott. This choice occurred because the agenda for advancing democracy was hampered by the existing political structure and system. Political democracy is in decline. The protest movement is aimed at the rulers and elites who are benefiting from the current democratic climate. The choice of pro-democracy activists to realize substantial democracy, which is aspired to in the ten resolutions of the 2019 Golput White Paper